Disaster disparities and differential recovery in New Orleans - Finch, Christina; Emrich, Christopher T.; Cutter, Susan L. (Population and Environment, 2010)
The historical disparities in the socio-demographic structure of New Orleans shaped the social vulnerability of local residents and their responses to Hurricane Katrina and its aftermath. These disparities, derived from race, class, gender, and age differences, have resulted in the uneven impact of the catastrophe on various communities in New Orleans, and importantly, their ability to recover. This article examines how the pre-existing social vulnerabilities within New Orleans interacted with the level of flood exposure to produce inequities in the socio-spatial patterns of recovery. Utilizing a combination of statistical and spatial approaches, we found a distinct geographic pattern to the recovery suggesting that the social burdens and impacts from Hurricane Katrina are uneven—the less flooded and less vulnerable areas are recovering faster than tracts with more vulnerable populations and higher levels of flooding. However, there is a more nuanced story, which suggests that it is neighborhoods in the mid-range of social vulnerability where recovery is lagging. While private resources and government programs help groups in the high and low categories of social vulnerability, the middle group shows the slowest rates of recovery. Further, it appears that the congressionally funded State of Louisiana Road Home Program (designed to provide compensation to Louisiana’s homeowners who suffered impacts by Hurricanes Katrina and Rita for the damage to their home) is not having a significant effect in stimulating recovery within the city.

Groundwater contribution to river flows – using hydrograph separation, hydrological and hydrogeological models in a southern Quebec aquifer - Larocque, M.; Fortin, V.; Pharand, M. C.; Rivard, C. (Groundwater hydrology/Modelling approaches, 2010)
Abstract. Groundwater contribution to river flows, generally called base flows, often accounts for a significant proportion of total flow rate, especially during the dry season. The objective of this work is to test simple approaches requiring limited data to understand groundwater contribution to river flows. The Noire river basin in southern Quebec is used as a case study. A lumped conceptual hydrological model (the MOHYSE model), a groundwater flow model (MODFLOW) and hydrograph separation are used to provide estimates of base flow for the study area. Results show that the methods are complementary. Hydrograph separation and the MOHYSE surface flow model provide similar annual estimates for the groundwater contribution to river flow, but monthly base flows can vary significantly between the two methods. Both methods have the advantage of being easily implemented. However, the distinction between aquifer contribution and shallow subsurface contribution to base flow can only be made with a groundwater flow model. The aquifer renewal rate estimated with the MODFLOW model for the Noire River is 30% of the recharge estimated from base flow values. This is a significantly difference which can be crucial for regional-scale water management.
Keywords: Ouvrage_Collectif_Numéro1

River flood plains are model ecosystems to test general hydrogeomorphic and ecological concepts - Tockner, Klement; Lorang, Mark S.; Stanford, Jack A. (River Research and Applications, 2010)
Abstract A major challenge in ecology is to link patterns and processes across different spatial and temporal scales. Flood plains are ideal model ecosystems to study (i) the processes that create and maintain environmental heterogeneity and (ii) to quantify the effects of environmental heterogeneity on ecosystem functioning and biodiversity. Fluvial processes of cut‐and‐fill alluviation create new channels, bars and benches within a flood plain that in turn provides new surface for subsequent vegetative recruitment and growth resulting in a shifting mosaic of interconnected aquatic and terrestrial habitat patches. Composition and spatial arrangement of these habitat patches control the movement of organisms and matter among adjacent patches; and the capacity of a habitat to process matter depends on the productivity of adjacent patches and on the exchange among these patches. The exchange of matter and organisms among habitats of different age and productivity is often pulsed in nature. Small pulses of a physical driver (e.g. short‐term increase in flow) can leach large amounts of nutrients thereby stimulating primary production in adjacent aquatic patches, or trigger mass emergence of aquatic insects that may in turn impact recipient terrestrial communities. Hence, biodiversity in a river corridor context is hierarchically structured and strongly linked to the dynamic biophysical processes and feedback mechanisms that drive these chronosequences over broad time and space scales. Today, the active conversion of degraded ecosystems back to a more heterogeneous and dynamic state has become an important aspect of restoration and management where maintaining or allowing a return to the shifting habitat mosaic dynamism is the goal with the expected outcome greater biodiversity and clean water among other valuable ecosystem goods and services. Copyright © 2009 John Wiley & Sons, Ltd.
Keywords: Ouvrage_Collectif_Numéro1